2014
DOI: 10.1016/j.ijfoodmicro.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Field Gel Electrophoresis characterization of Listeria monocytogenes isolates from cheese manufacturing plants in São Paulo, Brazil

Abstract: This study aimed to evaluate the occurrence of Listeria monocytogenes in cheese and in the environment of three small-scale dairy plants (A, B, C) located in the Northern region state of São Paulo, Brazil, and to characterize the isolates using conventional serotyping and PFGE. A total of 393 samples were collected and analyzed from October 2008 to September 2009. From these, 136 came from dairy plant A, where only L. seeligeri was isolated. In dairy plant B, 136 samples were analyzed, and L. innocua, L. seeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 40 publications
1
30
0
7
Order By: Relevance
“…Similar results were observed in a posterior study with human clinical specimens [18]. Recent studies also described the high occurence of 4b serotype in dairy products [17,30], ready-to-eat vegetables [31] and meat products retailed [6] in Brazil. Although the wide distribution of serotype 4b has been described in Brazil, details about the occurrence of ECs and your association with sporadic cases or outbreaks is ignored.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were observed in a posterior study with human clinical specimens [18]. Recent studies also described the high occurence of 4b serotype in dairy products [17,30], ready-to-eat vegetables [31] and meat products retailed [6] in Brazil. Although the wide distribution of serotype 4b has been described in Brazil, details about the occurrence of ECs and your association with sporadic cases or outbreaks is ignored.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies reported they are sources of contamination in cheeseprocessing plant environment (Dias et al 2012;Barracelli et al 2014) and small-sized yogurt plant (Cusato et al 2013) as well as restaurants (Ajala et al 2010). In fact, all samples have been purposefully manipulated under inadequate sanitary conditions; consequently, high counts of mesophilic aerobes and coliform bacteria at 35 and 45C were found, with values above 6 log cfu/g and 10 2 MPN/g, respectively.…”
Section: Microbiological Analysesmentioning
confidence: 99%
“…Previous studies on foodborne pathogens in dairy processing focused on Listeria monocytogenes and Escherichia coli O157:H7 (Almeida et al, 2013;Barancelli et al, 2014;Cagri-Mehmetoglu et al, 2011). However, reports on S. aureus in goat milk powder processing plants are relatively scanty.…”
Section: Introductionmentioning
confidence: 99%